An assessment of the effect of gender identity on the consumption of alcoholic beverages advertising: a case of Delta Beverages - Mugwati, Tapera (Midlands State University, 2017)
The purpose of the study is to assess the effect of gender identity on the consumption of alcoholic beverages advertising in Zimbabwe’s Delta Beverages. The research therefore sought to establish if males and females interpret alcohol advertisements the same. The way males and females interpret alcohol advertisements was analysed to assess if gender identity plays any role in the consumption of alcoholic beverages advertisements. The research also aimed to evaluate if masculinity and femininity affect information processing of alcohol advertisements and furthermore to analyze if gender values and beliefs have an effect on how males and females derive meaning from alcohol advertisements. A sample size of 381 participants was drawn from a population of 48.691 male and female alcohol consumers. Exploratory and descriptive research design was used to gain broader knowledge of the participants and to describe the characteristics of the population understudy. Questionnaires and interviews were used in conjunction with two picture advertisements to gather necessary information. Finally the research hypothesises that gender has an effect on consumption and therefore gender equality could increase the company’s market share. The objectives intend to identify gender inequality as well to promote gender equality in alcoholic beverages advertisements. The tools for data collection encompass a closed ended questionnaire targeted to the alcoholic beverages consumers, interviews with trade customers. The study concludes that there is gender inequality in the advertisement of alcoholic beverages. As such the need for Delta Corporation to exercise equality as indicated by both males and females participants cannot be over emphasized.